2022
DOI: 10.1002/suco.202100219
|View full text |Cite
|
Sign up to set email alerts
|

Flexural performance of circular concrete‐filled double steel tubular members: Testing, modeling, and strength predictions

Abstract: This paper presents experimental and numerical investigations on circular concrete‐filled double steel tubular (CFDST) members under flexural load. Seven specimens including five CFDST specimens were tested and the test parameters included the effects of concrete compressive strength, the thickness of the steel tubes, and the diameter ratio on their flexural performance. The final failure modes, moment (M)‐curvature (ϕ) curves, deflection curves of specimens, and distributions of section longitudinal strains w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…into CFSTs, thus the steel-reinforced concrete-filled steel tubes (SRCFSTs) are formed. [5][6][7][8][9][10][11][12][13] Existing research results have confirmed that some types of steel reinforcing elements (such as reinforcement cages, latticed steel angles, steel tubes, etc.) can provide an additional confining effect on the enclosed concrete, 5,6,12,13 hence the bearing capacity and ductility of SRCFSTs can be improved.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…into CFSTs, thus the steel-reinforced concrete-filled steel tubes (SRCFSTs) are formed. [5][6][7][8][9][10][11][12][13] Existing research results have confirmed that some types of steel reinforcing elements (such as reinforcement cages, latticed steel angles, steel tubes, etc.) can provide an additional confining effect on the enclosed concrete, 5,6,12,13 hence the bearing capacity and ductility of SRCFSTs can be improved.…”
Section: Introductionmentioning
confidence: 94%
“…In recent years, to improve the compression and shear properties of the core concrete in CFSTs, some scholars have added different types of steel reinforcing elements (such as the reinforcement cages, profiled steels, steel tubes and lattice steel angles, etc.) into CFSTs, thus the steel‐reinforced concrete‐filled steel tubes (SRCFSTs) are formed 5–13 . Existing research results have confirmed that some types of steel reinforcing elements (such as reinforcement cages, latticed steel angles, steel tubes, etc.)…”
Section: Introductionmentioning
confidence: 96%
“…The concrete-filled double steel tubular (CFDST) column, composed of the circular section, offers improved axial strength, ductility, and energy absorptions compared to its CFST counterparts and, therefore, has significant potential to be widely applied in future constructions, especially in highintensity earthquake areas [1][2][3][4]. Besides, CFDST column facilitates the selection of eco-friendly and green concrete, reducing the adverse impact of concrete on the environment [5].…”
Section: Introductionmentioning
confidence: 99%